2018
DOI: 10.1016/j.csbj.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of dyslipidemia using gene mutations, family history of diseases and anthropometric indicators in children and adolescents: The CASPIAN-III study

Abstract: Dyslipidemia, the disorder of lipoprotein metabolism resulting in high lipid profile, is an important modifiable risk factor for coronary heart diseases. It is associated with more than four million worldwide deaths per year. Half of the children with dyslipidemia have hyperlipidemia during adulthood, and its prediction and screening are thus critical. We designed a new dyslipidemia diagnosis system. The sample size of 725 subjects (age 14.66 ± 2.61 years; 48% male; dyslipidemia prevalence of 42%) was selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 85 publications
(101 reference statements)
1
13
0
Order By: Relevance
“…The differences may well be due to the effects of geographical and ethnic dissimilarities between populations of the studies. In conformity with our finding of dyslipidemia, an Iranian study which evaluated 725 children and adolescents demonstrated the relationship of LPL Hind III [rs320] and abnormal lipid levels ( Marateb et al, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…The differences may well be due to the effects of geographical and ethnic dissimilarities between populations of the studies. In conformity with our finding of dyslipidemia, an Iranian study which evaluated 725 children and adolescents demonstrated the relationship of LPL Hind III [rs320] and abnormal lipid levels ( Marateb et al, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, a medical diagnosis system is clinically reliable if Se ≥ 80%, Sp ≥ 95% [ 83 ], PPV ≥ 95% [ 46 ], and DOR ≥ 100 [ 84 ]. The proposed diagnosis system fulfilled three conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified individual risk factors of dyslipidemia and developed risk models depending on the questionnaire including dietary, lifestyle, anthropometric data and genetic markers 710. However, researches on dyslipidemia prediction were mainly based on cross-sectional studies for disease diagnosis and screening.…”
Section: Introductionmentioning
confidence: 99%